An Empirical Study on the External Environment, Brand Expansion Strategy, and Core Competence of Business (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the global economy led by the Fourth Industrial Revolution (4IR), innovation is taking place in all fields around the keywords of Internet and digital. It is changing from an information society to a precisely connected network society. The knowledge and skills that have been accumulated over the years are becoming the basis for creating new values and competitiveness on companies. These movements have a great influence on a company's marketing strategy and core competencies. With a new paradigm, brand expansion strategies are rapidly emerging from value-oriented and consumer-oriented management. Global companies should have a deep understanding of the new corporate management direction of comprehensive brand strategy management. In the era of the 4th industrial revolution, companies are constantly required to change a paradigm suitable for environmental changes. In a business environment that values network based on the Fourth Industrial Revolution, the satisfaction of various consumers should be achieved by considering individuality and cultural value rather than the nature of the product. A company with core competencies and marketing expansion strategies that share with consumers in real time will succeed. Therefore, it is possible to define the factors of the external environment of the company and suggest a strategic paradigm for brand expansion strategies and core competencies in the era of the 4IR. Based on empirical research, the implications for companies in this era of the 4th industrial revolution and the measures to secure core competencies were analyzed together. For the empirical analysis of the collected data, basic statistics were conducted using SPSS 22.0, and hypothesis testing was performed using the Smart PLS 2.0 statistical package. The results can be summarized as follows. First, industrial competitiveness had a significant influence on brand expansion strategies. Second, environmental uncertainty had a significant influence effect on brand expansion strategies. Third, the technology structure had a significant influence on brand expansion strategies. Fourth, brand expansion strategies had a significant influence effect on core competencies. In conclusion, we draw implications on the effects of the external environmental factors on brand expansion strategies and core competencies in the Fourth Industrial Revolution.